Improving Quality of Life in Hemodialysis Patients with Intradialysis Hypertension Using “SEHAT” Nursing Interventions - Yunie Armiyati; Suharyo Hadisaputro; Shofa Chasani; Untung Sujianto (Universitas Muhammadiyah Semarang, 2021)
Intradialytic hypertension can reduce the quality of life in hemodialysis patients. Providing appropriate nursing interventions will reduce morbidity, and improve the quality of intradialytic hypertensive patients. Provision of “SEHAT” nursing intervention package in the form of providing support, education and empowering, holistically with attention to therapeutic sensitivity can be applied to overcome patients problems. The purpose of the study was to analyze the